STUDI KASUS KEMAMPUAN MENULIS DENGAN GAYA BELAJAR KINESTETIK ANAK USIA 4-5 TAHUN DI TK MA’ARIF NU HASANUDIN SURABAYA Kayla Hefiza Fitrah, Dewi Komalasari, Kartika Rinakit Adhe, Muhammad Reza - Kayla Hefiza Fitrah; Dewi Komalasari; Kartika Rinakit Adhe; Muhammad Reza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of kinesthetic learning style on the writing process and outcomes of children aged 4–5 years at TK Ma’arif NU Hasanudin Surabaya. This research employs a qualitative approach with a single instrumental case study. The subject is a 4-year-8-month-old boy (RF). Data were collected through observation, teacher interviews, and documentation, and analyzed using the Miles and Huberman model with triangulation. The results show that RF’s writing process involves physical activities such as arranging beads into letters, walking along letter patterns on the floor, and using hand gestures to form letters. These activities effectively improve motivation, understanding, and letter retention. RF’s writing ability has developed, particularly in forming straight and curved lines as well as simple letters, although neatness still needs improvement. RF also frequently plays with objects while writing as a strategy to maintain focus. This study concludes that movement-based and experiential learning strategies are highly effective for kinesthetic learners. Therefore, teachers are encouraged to integrate physical activities and concrete media into writing instruction.